Analysis of Model fit and Item Parameter of Mathematics National Examination Using Item Response Theory - Aristiawan; Heri Retnawati; Edi Istiyono (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This study aims to determine the compatibility of the item response theory models in Mathematics National Exam and to find out the estimated parameters of the items. Qualitative analysis was carried out on the responses of 3223 students in Yogyakarta. The analysis was carried out using statistical and graph methods. Based on the results of the model suitability analysis, it was found that the model suitable for the Mathematics National Examination was a three-parameter logistic model (3 PL). The difficulty in the range of -0.887 to 1.013, discrimination between 0.78 - 3.551 and pseudo guessing between 0.181 to 0.5.